Self-Help Plus for refugee mothers in Rhino Refugee Settlement, Uganda (SEED): study protocol for a cluster-randomized controlled trial assessing intergenerational effects on preschool-aged children - Vassiliou, Phaidon T. B.; Ainamani, Herbert E.; Döring, Stefan; Gredebäck, Gustaf; Leku, Marx R.; Peltonen, Kirsi; Scharpf, Florian; Sen, Umay; Sutter, Matthias; Walsh, James Igoe; Hecker, Tobias; Hall, Jonathan (BioMed Central, 2026)
Background
Growing up in adversity can create enduring deficits in children’s cognitive and socio-behavioral skills that undermine later-life productivity, reduce human capital, and increase social costs. Early interventions that target caregiver mental health offer a promising pathway to strengthen the developmental environment of children exposed to severe stress. Yet, in low-resource humanitarian settings, evidence on scalable approaches that generate such intergenerational benefits remains limited. War-related displacement places mothers and young children at exceptional risk for psychological distress and impaired functioning, with potential long-term consequences for both generations. Self-Help Plus (SH+), a brief, low-intensity WHO group intervention based on Acceptance and Commitment Therapy, has shown promising short-term effects in reducing psychological distress among South Sudanese refugee women in Rhino Camp, Uganda. However, key questions remain regarding the durability of these effects and whether improvements in maternal mental health translate into measurable gains in children’s own wellbeing and early development.
Methods
This two-arm, parallel-group cluster-randomized controlled trial will enroll 720 mother-preschool-aged child (3–5 years) dyads from 24 villages in Rhino Refugee Settlement, Uganda. Villages are randomized 1:1 to receive either SH+ and Enhanced Usual Care (EUC), or EUC only. Assessments are conducted at baseline (T0), 3 months (T1), and 12 months (T2) post-intervention. The primary outcome is maternal psychological distress (Kessler-6) at 12 months (T2). The key secondary outcome is parent-reported child psychosocial wellbeing (Kiddy-KINDLR) at T2. Secondary outcomes include additional indicators of maternal wellbeing and mental health, parenting practices, and child outcomes assessed across study time points, including psychosocial difficulties and child self-reported wellbeing. Analyses will follow an intention-to-treat approach, adjusting for clustering and relevant covariates.
Discussion
This trial replicates and extends prior evidence on SH+ in a large refugee population. It will examine whether early mental health gains are sustained, and whether intergenerational benefits emerge for preschool-aged children. Findings will inform scalable intervention strategies to promote psychological resilience and child development in humanitarian contexts.